Associations of migraines with suicide ideation or attempts: A meta-analysis - Wei, Huijie; Li, Yu; Lei, Hua; Ren, Junwei (Frontiers in Public Health, 2023)
Objective Whether migraine is associated with a higher risk of suicide ideation and/or attempts remains controversial. Therefore, we aimed to evaluate these potential associations in migraine patients by performing a meta-analysis of previously published data. Methods We searched for studies published up to 31 June 2022 that compared the risk of suicide ideation/attempt in migraineurs and non-migraineurs in PubMed, EMBASE, and Web of Science databases. Sixteen studies fulfilled the eligibility criteria. We applied Random-effects models to calculate pooled adjusted odds ratios (AORs) and 95% confidence intervals (CIs) in patients with migraine. Results Migraine patients were at a significantly increased risk of suicide ideation (AOR 1.33, 95% CI 1.15–1.54) and suicide attempts (AOR 1.70, 95% CI 1.42–2.03). The increase in risk may be greater in adults (>19 years) than in younger individuals. Conclusion The available evidence indicates a significant association of migraines with suicide ideation and attempts. Future work should confirm and extend these findings, as well as explore whether they are affected by ethnicity or geography.